2005
DOI: 10.1007/s00146-005-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into influence of negative attitudes toward robots on human–robot interaction

Abstract: Negative attitudes toward robots are considered as one of psychological factors preventing humans from interacting with robots in daily life. To verify their influence on humans' behaviors toward robots, we designed and executed experiments where subjects interacted with Robovie, which is being developed as a platform for research on the possibility of communication robots. This paper reports and discusses the results of these experiments on correlation between subjects' negative attitudes and their behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
253
3
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 386 publications
(291 citation statements)
references
References 9 publications
16
253
3
9
Order By: Relevance
“…We also administered the "Negative Attitude towards Robots Scale" (NARS) which comprises three subscales: S1 which measures negative attitudes towards interactions with robots, S2 which measures negative attitudes towards the "social influence of robots," and S3 (an inverse scale) which measures positive attitudes towards emotions with robots [32]. NARS has been used to help explain differences found in other measures [40].…”
Section: Negative Attitude Towards Robots Scale (Nars)mentioning
confidence: 99%
See 1 more Smart Citation
“…We also administered the "Negative Attitude towards Robots Scale" (NARS) which comprises three subscales: S1 which measures negative attitudes towards interactions with robots, S2 which measures negative attitudes towards the "social influence of robots," and S3 (an inverse scale) which measures positive attitudes towards emotions with robots [32]. NARS has been used to help explain differences found in other measures [40].…”
Section: Negative Attitude Towards Robots Scale (Nars)mentioning
confidence: 99%
“…We used methods from [32] to perform our analysis using NARS. We divided the participants into subgroups according to the medians of each of the three NARS subscales S1, S2, and S3.…”
Section: Negative Attitude Towards Robots Scale (Nars)mentioning
confidence: 99%
“…Negative Attitudes Towards Robots Scale For the RIF and RIC, we also assessed the negative attitudes towards robots scale [15].…”
Section: Methodsmentioning
confidence: 99%
“…investigated the difference in relations of robots' appearances to emotions toward them between children and adults, using a questionnaire-based method and photographs of several robots. In addition, Bartneck et al (2005a; reported the influences of cultural differences and personal experiences with robots into attitudes toward robots by using a psychological scale measuring negative attitudes toward robots (Nomura et al, 2006a). The above studies are based on social research.…”
mentioning
confidence: 99%
“…Walters et al (2005) experimentally investigated relations between humans' personal traits measured by some questionnaires and behaviours toward robots such as permitted distances between them. Furthermore, Nomura et al (2006a) experimentally investigated relations between humans' negative attitudes toward robots and communication avoidance behaviours toward them. The studies mentioned above show an increase of psychological research on humanrobot interaction.…”
mentioning
confidence: 99%